Conceptions about sexual reproduction in Philo of Alexandria and their Greek scientific antecedents - Pérez, Laura (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2015)
This work intends to analyze the infl uence of the Greek scientifi c knowledge produced in the fi elds of biological, physiological and medical studies over the Hellenistic Jewish philosopher Philo of Alexandria, through an examination of his conceptions about the process of human sexual reproduction and, in particular, about the issue of the participation and role of men and women in gestation. In the fi rst place, we study the different theories about this subject which circulated in the Greek world: the traditional views expressed in tragedy, the theories of the pre-Socratic philosophers, of Hippocratic medicine and of Aristotle. Then, we analyze the ideas expressed by Philo about this matter, we investigate which of the Greek theories exerted greater infl uence over his thought and we try to explain why Philo appropriates some of these theories while discards others.
Keywords: sexual reproduction; pre-Socratics; Hippocratic medicine; Aristotle; Philo of Alexandria.